Study on the Hydrodynamic Effects of Bridge Piers Under Velocity-Type Pulse Ground Motion Based on Different Characteristic Periods - Gaojie Yun; Chunguang Liu (Applied Sciences)
This study was based on a target spectrum (GB183062015) and synthesized different characteristic periods, pulse ground motions, and non-pulse ground motions utilizing EQsignal v1.2.1 software. It also investigated the dynamic behaviors of bridge piers in seismic motions with varying characteristic periods, pulse and non-pulse effects, and the influence of 0 m and 10 m water depths. The findings indicated that the peak acceleration and stress behaviors vary significantly under different characteristic periods of ground motion. The maximum error in peak acceleration behavior of a bridge pier under ground motions of varying characteristic periods is 19.25%, while the maximum error in peak stress response is 11.35%. The acceleration and stress behaviors of a bridge pier under pulse ground motion action are more considerable than those under non-pulse seismic motion action. When the characteristic period is 0.40 s, the maximum error in peak acceleration of the bridge pier structure under pulse seismic motion and non-pulse seismic motion action is 86.08%, with the maximum error of the peak stress reaches 80.68%. The existence of water serves to minimize the natural frequency of the bridge pier. The pulse effects result in a maximum error of 40.49% for the peak acceleration and a maximum discrepancy of 323.08% for the peak stress of the bridge pier. The hydrodynamic effects result in a maximum error of 33.51% for the acceleration peak and 12.90% for the stress peak of the bridge pier. The effect of the pulse symptoms on the dynamic behavior of the bridge pier is considerably more pronounced than that of the hydrodynamic effects, with an intricate and complex influencing mechanism. In bridge flood protection and seismic design and optimization, it is essential to consider the impact of pulse seismic motion with varying characteristic periods.